2021
DOI: 10.3390/ijerph18094701
|View full text |Cite
|
Sign up to set email alerts
|

We’re Not Gonna Fall: Depressive Complaints, Personal Resilience, Team Social Climate, and Worries about Infections among Hospital Workers during a Pandemic

Abstract: Maintaining hospital workers’ psychological health is essential for hospitals’ capacities to sustain organizational functioning during the COVID-19 pandemic. Workers’ personal resilience can be an important factor in preserving psychological health, but how this exactly works in high stakes situations, such as the COVID-19 pandemic, requires further exploration. Similarly, the role of team social climate as contributor to individual psychological health seems obvious, but how it exactly prevents workers from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 75 publications
0
13
0
1
Order By: Relevance
“…Through resilience, emotion-focused strategies were negatively related to psychological distress directly and indirectly in a sample of Spanish nurses [ 42 ]. Resilience was negatively correlated with depression, stress and anxiety [ 44 , 46 , 54 , 65 , 68 , 71 ]. Age, work experience and level of education had a significant positive correlation with nurses’ resilience score [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through resilience, emotion-focused strategies were negatively related to psychological distress directly and indirectly in a sample of Spanish nurses [ 42 ]. Resilience was negatively correlated with depression, stress and anxiety [ 44 , 46 , 54 , 65 , 68 , 71 ]. Age, work experience and level of education had a significant positive correlation with nurses’ resilience score [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…As evidenced by previous research, psychological resilience is a fundamental variable in reducing and preventing the negative psychological effects of the pandemic [ 18 ]. In our review, we found that resilience is associated with lower levels of depression, anxiety and burnout [ 44 , 46 , 53 , 54 , 65 , 68 , 71 ]. Resilience improves personal growth and perceived professional benefits [ 33 , 53 ] and has a positive impact on work engagement even in non-healthcare workers [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the scope of questions related to pandemic concern was limited in our study, more precise explanations of this remarkable result are not possible. There is evidence that resilience [ 71 , 72 ] can mediate pandemic-related concerns. However, our data also do not allow us to draw conclusions about the causes or determinants of the rather moderate level of worry and the lack of association with perceived stress.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside coping with psychosocial stressors from their personal worries and concerns associated with COVID-19 (Fleuren et al, 2021;Taylor et al, 2020), MHWs bear the professional responsibility of responding to increased demand and rapidly adapting their mental health service models, which have experienced significant disruptions (Moreno et al, 2020;WHO, 2020a). With a view to contain COVID-19, remote tele-therapies have largely replaced in-person sessions (Scottish Government, 2020;Whaibeh et al, 2020).…”
Section: Challenges Faced By Mental Health Workers During Covid-19mentioning
confidence: 99%